The Role of Numerical Methods in the Sensitivity Analysis of a Density Parameter in a Passivation Rate Interaction - EN Ekaka-a; EO Chukwuocha; NM Nafo (Journal of Applied Sciences and Environmental Management)
The mathematical modelling of physiochemical interaction in the framework of industrial and environmental physics which relies on an initial value problem is defined by a first order ordinary differential equation. Two numerical methods of studying sensitivity analysis of physiochemical interaction data are developed. This mathematical technique is used to investigate the extent of the sensitivity of the density parameter over a time interval.